Designing products that facilitate easy and intuitive repair, an implementation in product design education - Parmentier, Davy; Dumon, Louise; Detand, Jan (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
When considering circular economy, reuse, refurbish and repair of products is key in many circular business models. Both efficient and intuitive disassembly and assembly are crucial facilitators for these strategies, impacting feasibility, cost and economic viability. Thus, product designers and product design educations should focus on how to design products for easy and intuitive disassembly and reassembly to facilitate repairability. The focus from design educations on these specific processes is however very limited. This paper elaborates on the outcomes of a project-based learning course for design engineering students. The students redesigned an electric device (power tool or household appliance) with special attention to design for repairability strategies. Necessary frameworks and tools were offered to first analyze the disassembly and assembly process of the product and secondly redesign for repair. Unlike many other methods that are about assessing assembly and disassembly processes in terms of the time needed to perform them, here special attention was paid to the interactions, both cognitive and physical, during repair. This premise aligns better with the context of end-user repair where time is less relevant but where interactions need to be easier and more intuitive. Through case studies, it was investigated whether this focus generated valuable results and was feasible to implement. The paper is especially relevant for those concerned with circular product design, the assembly and disassembly of products linked to circular strategies such as repair and the integration within design engineering curricula.